Construction of Compound Sentence Phenomenon in Agoda.com Reviews - I Dewa Ayu Salsa Bila Ninda Pradevi,; Putu Devi Maharani, (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Compound sentence, as a type of sentence structure, are sometimes considered easy to construct due to their limited range of conjunction options, such as for, and, nor, but, or, yet, so along with punctuation marks, such as semicolons (;) and commas (.) to bridge the clauses. However, the fact of its use is often inappropriate, especially in written form. The primary objective of this study is to identify the construction of coordination used in the compound sentences found in the reviews of The Apurva Kempinski Bali on Agoda.com website. Additionally, the study aims to analyze the constituent structure of each compound sentence using tree diagrams. The data of this study were taken from period of time April until July 2024. The data were analyzed by using the observation method and qualitative descriptive methods. To analyze the types of coordination in compound sentences, this study applied the theory proposed by Quirk and Greenbaum (1973). The constituent structure of each compound sentence was analyzed by using tree diagram theory proposed by Brown and Miller (1991). The result of this study show that there are three types of coordination in compound sentence: syndetic coordination, asyndetic coordination, and a combination of both types. Out of 40 data of compound sentences, there are 21 data that contain syndetic coordination, 15 data contain asyndetic coordination, and 4 data contain asyndetic coordination. The dominant type of coordination used is syndetic coordination. However, there is a type in which the sentence construction seems to belong to another type such as syndetic coordination which looks like a combination coordination between syndetic and asyndetic coordination.